The effects of high-intensity interval training on lower-limb strength, VO₂max, vertical jump performance, and heart rate in college athletes - Japhet Ndayisenga; Lionel Nzohabonimana (Journal of Coaching and Sports Science, 2026)
Background:  High-intensity interval training (HIIT) is a time-efficient, evidence-based modality capable of inducing substantial simultaneous physiological adaptations across multiple fitness domains. Despite a growing global evidence base for HIIT efficacy, scientifically validated programs for athletes in sub-Saharan African contexts, particularly Burundi, remain absent from the peer-reviewed literature. Aims: This study designed, validated, and evaluated the effectiveness of a five-week HIIT program targeting lower limb strength, maximal oxygen uptake (VO₂max), vertical jump performance, and resting heart rate (RHR) among college athletes. Methods: A pre-experimental one-group pre-test post-test design was employed with 72 college athletes (n = 72). The HIIT program comprised four specialized modules delivered in three sessions per week over five weeks. Pre- and post-test assessments used the timed wall-sit test (lower limb strength), Beep Test and Cooper's 12-minute run (VO₂max), Sargent Jump Test and vertical force plate (vertical jump), and stopwatch pulse measurement (RHR). Data normality was confirmed via the Shapiro–Wilk test; paired-samples t-tests were conducted via IBM SPSS v23. Result: Statistically significant improvements were observed for all four variables following the intervention: lower limb strength (t(71) = −10.267, p < .001; +91.10%; Cohen's d = 1.210), VO₂max (t(71) = −12.070, p < .001; +14.51%; d = 1.422), vertical jump (t(71) = −17.763, p < .001; +23.82%; d = 2.093), and resting heart rate (t(71) = 18 Conclusion: The five-week multi-component HIIT program produced highly significant, large-effect improvements across all four fitness domains in 72 university students, constituting the first large-sample, institutionally validated HIIT program in the Burundian sports science context and offering a scalable, evidence-based model for athletic physical development in resource-limited African settings.